2019
DOI: 10.36359/scivp.2019-20-2.30
|View full text |Cite
|
Sign up to set email alerts
|

Гістологічні Та Гістохімічні Зміни В Нирках Собак За Отруєння Ізоніазидом

Abstract: У статті представлені результати макроскопічних, гістологічних та гістохімічних досліджень нирок собак за отруєння ізоніазидом. Проведено патологоанатомічний розтин 19 трупів собак різного віку та породи, відібрано фрагменти нирок для морфологічних досліджень. Взірці нирок фіксували в 10 % водному розчині нейтрального формаліну, рідині Карнуа і Буена. Зневоднення проводили в етанолі зростаючої концентрації та заливали в парафін. Зрізи виготовляли на мікротомі МС–2 товщиною 7 мкм, фарбували гематоксиліном та ео… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…If pesticides get into the body of a dog, the following symptoms of intoxications develop: gastrointestinal atony, tachycardia, dyspnea, and convulsions. Acute intoxication pathomorphological manifestations include passive congestion of the liver, kidneys, and spleen, acute dilatation of the stomach and blind gut; in case of chronic intoxication caused by imidacloprid-containing pesticides, hydropic degeneration is observed in the liver and kidneys; in case of intoxication caused by cyanocontaining neonicotinoids, cloudy swelling, leukocyte infiltration, and connective tissue growth are observed [7]. It has been demonstrated that combined administration of unitiol in the amount of 0,025 g/kg and diazepam in the amount of 0,5 mg/kg helps to accelerate the biotransformation of pesticides and leads to the reduction their residual amount concentration in the body of a dog and increases the survival of animals up to 75-80% [6].…”
Section: Methodsmentioning
confidence: 99%
“…If pesticides get into the body of a dog, the following symptoms of intoxications develop: gastrointestinal atony, tachycardia, dyspnea, and convulsions. Acute intoxication pathomorphological manifestations include passive congestion of the liver, kidneys, and spleen, acute dilatation of the stomach and blind gut; in case of chronic intoxication caused by imidacloprid-containing pesticides, hydropic degeneration is observed in the liver and kidneys; in case of intoxication caused by cyanocontaining neonicotinoids, cloudy swelling, leukocyte infiltration, and connective tissue growth are observed [7]. It has been demonstrated that combined administration of unitiol in the amount of 0,025 g/kg and diazepam in the amount of 0,5 mg/kg helps to accelerate the biotransformation of pesticides and leads to the reduction their residual amount concentration in the body of a dog and increases the survival of animals up to 75-80% [6].…”
Section: Methodsmentioning
confidence: 99%